INTEGRÁLÓ ERŐK LEHETŐSÉGE A NEMZETKÖZI RENDSZERBEN FOGALMI ALAPVETÉS - Zsinka, László (Közép-Európai Közlemények, 2020)
What we today call the international system was created by the West from early modern age. This term is often used in political theory, but less focused on how to classify integrative forces within the international system. In the context of this study, we are attempting to lay down some conceptual basis. How do we understand the linking and unifying factors within the international system? Initially, the emergence of the international system was largely attributed to political factors in theory, but we can also refer to other explanatory principles: one considers economic factors and civilizational factors are taken into consideration as essential aspects of the international structures. According to our viewpoint, inter-civilization dialogue seems to be a "third way" that goes beyond the expansive one-sidedness of Western universalism and the world-level confrontation of hostile civilizations. This „civilizational approach” incorporates the two previous aspects - economic and political - and this is what gives its importance. In our view, inter-civilization dialogue is the only viable way to create global ethos, and only the resulting "intellectual revolution" can make national and supranational economic and political institutions to operate in effective way under the conditions of globalization.